Study of Smart Antenna Wide Band Multi Beam by Algorithm Switch Beam - Yuliarman Saragih; Ibrahim; Agatha Elisabet (Journal of Sustainable Engineering: Proceedings Series, 2019)
The use of wideband antennas in radio frequency (RF) systems are intended to improve the efficiency of the system economically. So that problems arise due to differences in RF system frequency allocation in each country can be overcome. Other than that, the need for an antenna that can optimize the direction of the beam becomes one which became a consideration, for that to develop a smart antenna that is capable of producing the different beam. In various studies, wideband antennas have been built only able to work on a single beam. Meanwhile, the antenna has also been proven to be working in multi-beam but still works on a single frequency. The researcher intends to develop an antenna that can work as a smart antenna that applies multi-beam with switching algorithms by having a wide working frequency (wideband). Multi-beam with wideband can be produced by combining wideband antenna array with a Butler matrix that applies the switching beam algorithm with phase array technique so that it can be a smart antenna because the antenna can be adjusted of the beam as desired.